Reer Review: The Analysis of Protection and Fulfillment The Rights of Person with Disabilities in Gunungkidul District of Yogyakarta Province - Arni Surwanti, Ahmad Ma'aruf (Proceeding ICOMS, 2016)
The efforts to fulfill the rights of person with disabilities in various aspects like in education The 2016 Intemational Conference Of Management Sciences 978-602-7 577-63-3 March 2016 Fakultas Ekonomi - UMY